45‐2: Invited Paper: Towards High‐Performance Organic Transistors for Display and other Applications. Issue 1 (28th June 2022) - Guo, Erjuan; Wu, Zhongbin; Liu, Yuan; Kleemann, Hans; Leo, Karl
Abstract : Organic semiconductor devices have potential for displays as light emitter and organic backplane transistors. We present vertical transistor structures with very short channel length without micropatterning. These devices are well suited to drive organic light‐emitting diodes (OLED), allowing all‐organic flexible displays. We have achieved kA/cm 2 current densities useful for bright OLED displays and record operating frequencies >40MHz /2/. Vertical organic light‐emitting transistors show efficient emission in different colors, combining OLED operation and switching and fully compatible with vacuum mass production. Vertical transistors have GHz potential using highly ordered layers grown quasi‐epitaxially.